Quality of life measurement instruments applied to kidney transplanted individuals (Research, Society and Development, 2021)
The objective of this research was to identify in the literature the instruments applied to measure the quality of life (QOL) in kidney transplant patients. This is a literature review carried out in the Pubmed, Science direct databases and in the Virtual Health Library (VHL) portal that identified publications that used Patient-Reported Outcome Measures (MRRP) in kidney transplantation. The corpus of analysis of this research was obtained by 23 articles, which presented different instruments for assessing QoL in kidney transplant recipients. It was possible to observe a low bibliographic production on this theme, with an average of 1.5 publications per year, considering the sample interval (1996-2021). The SF-36 was the predominant questionnaire among the analyzed studies, with the others having a generic approach with characteristics that diverged between the evaluator and the research objectives. Finally, this study pointed to the need for further research to assess the application of more specific instruments for this population so that the real needs of kidney transplant recipients are captured, contributing to patient-centered care.